2010
DOI: 10.1098/rsta.2010.0195
|View full text |Cite
|
Sign up to set email alerts
|

Designing biomimetic antifouling surfaces

Abstract: Marine biofouling is the accumulation of biological material on underwater surfaces, which has plagued both commercial and naval fleets. Biomimetic approaches may well provide new insights into designing and developing alternative, non-toxic, surfaceactive antifouling (AF) technologies. In the marine environment, all submerged surfaces are affected by the attachment of fouling organisms, such as bacteria, diatoms, algae and invertebrates, causing increased hydrodynamic drag, resulting in increased fuel consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
123
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(124 citation statements)
references
References 112 publications
(132 reference statements)
0
123
0
1
Order By: Relevance
“…artificially mimic these properties [47]. In another development, blue mussels use adhesive and byssal threads to quickly attach themselves to surfaces [48].…”
Section: Box 2 Option Value Of Biodiversitymentioning
confidence: 98%
“…artificially mimic these properties [47]. In another development, blue mussels use adhesive and byssal threads to quickly attach themselves to surfaces [48].…”
Section: Box 2 Option Value Of Biodiversitymentioning
confidence: 98%
“…3 In full-scale power trials for a naval frigate, 4 it has been found that fouling, mainly in the form of biofilms, caused an increase of 8%-18% in drag. Schultz, Swain, and co-workers [5][6][7][8] observed substantial fuel penalties resulting from increased surface roughness due to biofilms (in the range of 5 lm-1 mm, reviewed in Salta et al 9 ). Being part of a surface, biofilms will also be affected by these forces, and thus, it is imperative to better understand the effect of relevant hydrodynamic flow regimes 10 on the biofilm processes (i.e., bacterial attachment and initial biofilm formation).…”
mentioning
confidence: 97%
“…Perhaps the most thoroughly studied aspect of B. improvisus settlement behaviour is the response of cyprids to surface topography (Andersson et al 1999, Berntsson et al 2000a2000b;Berntsson et al 2004). Many surface features used in antifouling research have been designed to be biomimetic, inspired by the naturally occurring external structures of foulingfree organisms (Salta et al 2010;Scardino & de Nys 2011). Such structures are reproduced as 3-dimensional patterned surfaces fabricated from synthetic polymers (e.g.…”
Section: Introductionmentioning
confidence: 99%